Gut Microbiota and the Paradox of Cancer Immunotherapy - Poutahidis, Theofilos; Kleinewietfeld, Markus; Erdman, Susan (Frontiers in Immunology, 2014)
It is recently shown that beneficial environmental microbes stimulate integrated immune and neuroendocrine factors throughout the body, consequently modulating regulatory T lymphocyte phenotypes, maintaining systemic immune balance, and determining the fate of preneoplastic lesions towards regression while sustaining whole body good health. Stimulated by a gut microbiota-centric systemic homeostasis hypothesis, we set out to explore the influence of the gut microbiome to explain the paradoxical roles of regulatory T lymphocytes in cancer development and growth. This paradigm shift places cancer prevention and treatment into a new broader context of holobiont engineering to cultivate a tumor-suppressive macroenvironment.